2022
DOI: 10.7759/cureus.20863
|View full text |Cite
|
Sign up to set email alerts
|

Relapse and Outcome of Lupus Nephritis After Renal Transplantation in the Modern Immunosuppressive Era

Abstract: BackgroundRecurrence of lupus nephritis in the graft is a concern in lupus patients with end-stage renal disease undergoing renal transplantation. The recurrence of lupus nephritis has been variable among different studies depending on the patient characteristics, immunosuppressive regimen, and indications of renal biopsy. Therefore, we investigated the recurrence of lupus nephritis among our patients to see if the new post-transplant regimen has impacted the recurrence. MethodsWe collected data on all recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Historically, when patients with LN approached ESKD, the trend was for rheumatologists 2 and nephrologists 3 to start patients on hemodialysis and suspend kidney transplant in allowance for the quiescence of the underlying autoimmune processes of SLE and LN. However, recent studies demonstrated a lower risk of graft failure following recurrent LN 5,6,10 secondary to advancements in immunosuppressive therapies 5,6 and a lower risk of premature mortality among patients with LN-ESKD spending less time on dialysis prior to kidney transplant. 7,17,18 With kidney transplant now being a well-established treatment option for patients with LN-ESKD, it is vital that a concerted effort is put forth in understanding at what point in the disease process is this younger patient population initiating first steps to transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, when patients with LN approached ESKD, the trend was for rheumatologists 2 and nephrologists 3 to start patients on hemodialysis and suspend kidney transplant in allowance for the quiescence of the underlying autoimmune processes of SLE and LN. However, recent studies demonstrated a lower risk of graft failure following recurrent LN 5,6,10 secondary to advancements in immunosuppressive therapies 5,6 and a lower risk of premature mortality among patients with LN-ESKD spending less time on dialysis prior to kidney transplant. 7,17,18 With kidney transplant now being a well-established treatment option for patients with LN-ESKD, it is vital that a concerted effort is put forth in understanding at what point in the disease process is this younger patient population initiating first steps to transplant.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, studies conducted more recently report that due to advancements in post-transplant immunosuppressive therapies, only 2.5%-10.5% of patients with LN-ESKD will experience recurrent LN post-transplant. 5,6 Additionally, in a recent national study examining post-transplant outcomes among patients with LN-ESKD waitlisted for kidney transplant, authors reported a survival benefit associated with patients who received a kidney transplant compared to those that remained on the waitlist. 7 Finally, recommendations to intentionally delay kidney transplant are not standardized and are in direct contrast to literature for all-cause ESKD, which suggests a shorter time from ESKD diagnosis to kidney transplant leads to better post-transplant outcomes.…”
Section: Introductionmentioning
confidence: 99%